Establishment and Characterization of Canine Mammary Gland Carcinoma Cell Lines With Vasculogenic Mimicry Ability in vitro and in vivo - de Faria Lainetti, Patrícia [UNESP]; Brandi, Andressa [UNESP]; Leis Filho, Antonio Fernando [UNESP]; Prado, Maria Carolina Mangini [UNESP]; Kobayashi, Priscila Emiko [UNESP]; Laufer-Amorim, Renée [UNESP]; Fonseca-Alves, Carlos Eduardo [UNESP] (Frontiers, 2020)
Mammary tumors affect intact and elderly female dogs, and almost 50% of these cases are malignant. Cell culture offers a promising preclinical model to study this disease and creates the opportunity to deposit cell lines at a cell bank to allow greater assay reproducibility and more reliable validation of the results. Another important aspect is the possibility of establishing models and improving our understanding of tumor characteristics, such as vasculogenic mimicry. Because of the importance of cancer cell lines in preclinical models, the present study established and characterized primary cell lines from canine mammary gland tumors. Cell cultures were evaluated for morphology, phenotype, vasculogenic mimicry (VM), and tumorigenicity abilities. We collected 17 primary mammary carcinoma and three metastases and obtained satisfactory results from 10 samples. The cells were transplanted to a xenograft model. All cell lines exhibited a spindle-shaped or polygonal morphology and expressed concomitant pancytokeratin and cytokeratin 8/18. Four cell lines had vasculogenic mimicry ability in vitro, and two cell lines showed in vivo tumorigenicity and VM in the xenotransplanted tumor. Cellular characterization will help create a database to increase our knowledge of mammary carcinomas in dogs, including studies of tumor behavior and the identification of new therapeutic targets.
Keywords: cell culture; female dog; mammary tumor; oncology; veterinary